Comparison of filler-dependent mechanical properties of jute fiber reinforced sheet and bulk molding compound. (1st November 2018) - Lautenschläger, Miriam I.; Mayer, Lukas; Gebauer, Julian; Weidenmann, Kay A.; Henning, Frank; Elsner, Peter
Abstract: Growing environmental awareness means that natural fibers, such as jute fibers, are increasingly used as reinforcement in polymer composites. Sheet and bulk molding compound (SMC and BMC) are two examples. Besides reducing the costs, fillers are used in SMC and BMC to improve the physical properties during processing. The work presented here focuses on the influence of two fillers with different particle shape on the tensile and flexural properties of SMC and BMC. The effect of ashlar-shaped calcium carbonate and platy kaolin as fillers in jute nonwoven reinforced sheet molding compound (SMC) and jute chopped fiber reinforced bulk molding compound (BMC) was investigated. Scanning electron microscopy was used to evaluate the fractured surfaces. The SMC material revealed anisotropic properties and a reinforcing effect of kaolin as filler, whereas for the BMC material large scattering was observed.